Establishment and validation of a predictive nomogram for the risk of premalignant lesions in children with choledochal cyst - Ruyue Gao; Ruyue Gao; Meng Ke; Meng Ke; Jie Shi; Yandong Zhang; Jizhen Zou; Mei Diao; Long Li; Long Li; Long Li (Frontiers Media S.A., 2023)
BackgroundCholedochal cyst (CDC) increases the risk (2.5%-30%) of malignancy. Metaplasia and dysplasia have been recognized as premalignant lesions among CDCs. This study aimed to evaluate the risk factors of metaplasia and dysplasia in CDC children.MethodsTwo hundred and ten CDC children who underwent cyst excision and Roux-en-Y hepaticojejunostomy at our institution between July 2020 and November 2021 were included and randomly divided into the training set and validation set. Univariate and multivariate logistic regression analysis were used to identify independent risk factors of premalignant lesions in the training set and build a predictive nomogram. The performance and discriminatory abilities of the nomogram were further assessed and validated in the validation set.ResultsOf the 210 CDC children, 78 (37.1%) patients developed premalignant lesions. Age (OR, 1.011, 95%CI, 1.000-1.022, P = 0.046), symptoms duration (OR, 1.021, 95%CI, 1.001-1.042, P = 0.036), cyst diameter (OR, 1.737, 95%CI, 1.328-2.273, P < 0.001), recurrent attacks of biliary pancreatitis (OR, 3.653, 95%CI, 1.205-11.076, P = 0.022), and biliary operation history (OR, 5.860, 95%CI, 1.268-27.084, P = 0.024) were identified as independent risk factors. Based on these predictors, a predictive nomogram was generated. The AUC of the nomogram was 0.873 in the training set and 0.793 in the validation set, indicating that it was robust and well calibrated.ConclusionsA novel nomogram to the individualized risk of premalignant lesions in CDC children was successfully built, on the basis of age, symptoms duration, cyst diameter, recurrent attacks of biliary pancreatitis, and biliary operation history. This nomogram, combined with the final pathological results, can help clinicians to develop more efficient follow-up strategies for the high-risk children with CDC.